Kidney hemodynamic effects of sodium-glucose cotransporter 2 inhibitors in diabetes: physiology and clinical implications - León-Jiménez, David; Sridhar, Vikas S.; López-Mendoza, Manuel; Scholtes, Rosalie A.; Schmieder, Roland; Cherney, David Z.I.; van Raalte, Daniël H.; Toro-Prieto, Francisco J.; Miramontes-González, José Pablo; van Bommel, Erik J.M. (Clinical Kidney Journal, 2025)
The progressive loss of kidney function in diabetes mellitus is partly attributable to the occurrence of glomerular hyperfiltration. Consequently, therapeutic interventions that lower intra-glomerular pressure are a cornerstone of treatment in diabetic kidney disease. Sodium-glucose cotransporter 2 (SGLT2) inhibitors consistently reduce glomerular filtration rate (GFR) and calculated intraglomerular pressures across studies. However, the net effect on arteriolar tone that leads to acute GFR declines may differ between cohorts. While pre-glomerular vasoconstriction appears to be the dominant mechanism responsible for GFR dipping in patients with type 1 diabetes (T1D) and glomerular hyperfiltration, other factors, including post-glomerular vasodilation, may contribute to the acute GFR decline in normofilterering individuals with T1D and type 2 diabetes. Regardless of the responsible mechanisms, acute changes in GFR are associated with long-term kidney function preservation—a relationship that may reflect an underlying protective decline in glomerular hypertension.
CRIS-Team Scopus Importer:2025-01-31
Keywords: albuminuria; CKD; diabetic kidney disease; proteinuria; renin–angiotensin system